Innovating Jewelry Design Education in Vietnam in the 5.0 Era - Đỗ Vương Bích Tữu (Journal of Technical Education Science, 2025)
The 5.0 era is often referred to as the age of technology and super-intelligent society. This study focuses on improving the quality of education in Vietnam’s jewelry design industry amidst the rapid advancement of technology. The primary objective is to determine what can be done to enhance the training quality in this field for the future. The article adopts an interdisciplinary approach and employs the document analysis research method to provide a comprehensive view of the topic. The findings indicate that the digital age has created significant opportunities for innovative training approaches, ranging from investment in teaching methods to enhancing students’ creativity in jewelry design. While these developments present avenues for growth in the industry, they also bring challenges in modernizing education to keep pace with current trends. To improve the quality of training, the article proposes solutions to help training institutions balance maintaining traditional crafting techniques and maximizing the benefits of modern technology, at the same time, it is essential to ensure that students acquire the necessary working skills of a designer in the new era.